Chile : A Strategy To Promote Innovative Small And Medium Enterprises - Goldberg, Mike (The World Bank, 2008)
With its strong export orientation and emphasis on competitiveness, the Chilean economic model has been the envy of its neighbors for more than a decade. However, there are underlying vulnerabilities. Historically, exports have been concentrated in mining and agriculture, sectors dominated by large firms that do not generate a large share of employment. Small and medium enterprises play a key role in employment generation and economic decentralization in Chile, yet their employment was stagnant between 2000 and 2004. Based on work completed in 2003, this study provides a review of the Chilean government's substantial investment in programs that support small and medium enterprises. This review of government programs confirms the importance of coordination and an overarching strategy, in the form of a National Innovation System, led by a single institution. The review also finds that demand-driven programs were more likely to be sustainable. Finally, the study demonstrates that Chile (and other countries with many support programs for small and medium enterprises in place) needs an integrated management information system to analyze, assess, coordinate, and streamline the program portfolio for small and medium enterprises in the future